Proposed new branch and interior design scheme for Blincblinc Boutique at No G-C-2,G-C-3 at Greentown Square, Jalan Dato’ Seri Ahmad Said, Greentown 30450 Ipoh, Perak / Basyirah Mardhiah Zakaria - Zakaria, Basyirah Mardhiah (Faculty of Architecture, Planning and Surveying, 2009)
The main objective in proposing this proposal for Blinc Blinc Boutique new branch is to design a boutique with applying the concept of diamonds as it is suitable with Blinc Blinc which is aiming to attract more customers in the near future. Blinc Blinc wanted to be unique and outstanding and on the same line with other local and international label. Nowadays, the emerging of online boutiques are gaining the attention of Malaysians and it is not possible for Blinc Blinc to be an established brand in the next 5 years. The psychology aspect of space is also applied in the interior design and planning to attract the attention of the public in this new style of boutique. Normally, boutiques in Malaysia did not promote any special features in the boutique unlike the boutiques from the foreign countries. Besides that, the research compilation of data is collected to get the most precise and important information about Blinc Blinc Boutique and the proposal of the new design. The information is gathered from time to time to ensure the data is complete and useful for the use in the design phase. Every design is developed by taking into consideration of the issues and problem statements, issues that arises, the feedback from the customers and staffs and the collection of relevant data related with the project. Without issues and problems, the new design will not be able to be produced. With a new and improved design, the boutique will be the example of other boutiques in Malaysia. For this dinal project, there are a few researches that had been made, and a few design problems must be overcome. In the existing Blinc Blinc Boutique, it lacks in display system which is not very affective in attracting customers. And the color scheme that is used in the boutique is too dark causing the interior to look very dull and unattractive. The issue of the limited space was also a problem from the existing boutique. To solve this problem, the boutique will be proposed with a new display design system so it will attract more customers to shop at Blinc Blinc Boutique without changing the image it has now.